Lovastatin attenuates hypertension induced by renal tubule‐specific knockout of ATP‐binding cassette transporter A1, by inhibiting epithelial sodium channels. (30th July 2019) - Wu, Ming‐Ming; Liang, Chen; Yu, Xiao‐Di; Song, Bin‐Lin; Yue, Qiang; Zhai, Yu‐Jia; Linck, Valerie; Cai, Yong‐Xu; Niu, Na; Yang, Xu; Zhang, Bao‐Long; Wang, Qiu‐Shi; et al.
Abstract : Background and Purpose: We have shown that cholesterol is synthesized in the principal cells of renal cortical collecting ducts (CCD) and stimulates the epithelial sodium channels (ENaC). Here we have determined whether lovastatin, a cholesterol synthesis inhibitor, can antagonize the hypertension induced by activated ENaC, following deletion of the cholesterol transporter (ATP‐binding cassette transporter A1; ABCA1). Experimental Approach: We selectively deleted ABCA1 in the principal cells of mouse CCD and used the cell‐attached patch‐clamp technique to record ENaC activity. Western blot and immunofluorescence staining were used to evaluate protein expression levels. Systolic BP was measured with the tail‐cuff method. Key Results: Specific deletion of ABCA1 elevated BP and ENaC single‐channel activity in the principal cells of CCD in mice. These effects were antagonized by lovastatin. ABCA1 deletion elevated intracellular cholesterol levels, which was accompanied by elevated ROS, increased expression of serum/glucocorticoid regulated kinase 1 (Sgk1), phosphorylated neural precursor cell‐expressed developmentally down‐regulated protein 4‐2 (Nedd4‐2) and furin, along with shorten the primary cilium, and reduced ATP levels in urine. Conclusions and Implications: These data suggest that specific deletion of ABCA1 in principal cells increases BP by stimulating ENaC channels via a cholesterol‐dependent pathway which induces several secondary responses associated with oxidative stress, activated Sgk1/Nedd4‐2, increased furin expression, and reduced cilium‐mediated release of ATP. As ABCA1 can be blocked by cyclosporine A, these results suggest further investigation of the possible use of statins to treat CsA‐induced hypertension.